PENGARUH LINGKUNGAN KERJA, HUMAN RELATION DAN INSENTIF TERHADAP PRODUKTIVITAS KARYAWAN PADA BANK CIMB NIAGA MAKASSAR - Oktavin Datu Mikan Sampetoding; Abd Rahman Kadir; Sobarsyah Sobarsyah (Jurnal Bisnis dan Kewirausahaan, 2023)
The purpose of this research was to determine the effect of the work environment on employee productivity, the effect of human relations on employee productivity and the effect of incentives on employee productivity at Bank CIMB Niaga Makassar. This study uses a type of quantitative research. Quantitative research manages data in a statistical way by using actual data with a clear structure from the beginning to the creation of research methods. The population in this study is a generalization consisting of objects or subjects that have certain qualities determined by the researcher to be studied and then drawn conclusions. The population in this study were all employees at Bank CIMB Niaga Makassar, totaling 34 people. Data collection techniques in this study were observation and questionnaires. The data analysis technique in this study is the classical assumption test, data quality test, multiple linear regression test, correlation coefficient test, coefficient of determination test and partial test. Data management in this study uses the SPSS program.